PWE-287 Long term outcomes after biological mesh reconstruction of the pelvic floor following extra-levator abdominoperineal excision of rectum (APER). (22nd June 2015) - Bhalla, A; Peacock, O; Javanmard-emamghissi, H; Tou, S; Hurst, N; Speake, W; Tierney, G; Lund, J
Abstract : Introduction: Extra-levator abdominoperineal excision of the rectum (ELAPER) leaves a large pelvic floor defect requiring reconstruction. Our previous work has shown the benefits of biomesh repair over other techniques in the short term. The aim of this study is to determine long term outcomes of biological mesh pelvic floor reconstruction following ELAPER. Method: Prospective data was collected for consecutive patients having ELAPER for low rectal cancer at a single UK institution between October 2008 and March 2013. The perineum was reconstructed using a biological mesh (Surgisis® Biodesign™, Cook Medical). Short and long-term outcomes were evaluated and the pelvis clinically assessed for herniation, and computed tomography scans reviewed by a specialist gastrointestinal radiologist for disease recurrence. Results: Thirty-four patients (27 male, median age 62 years (range 40–72)) were included. Median operative time was 248 mins (range 120–340) with a median length of hospital stay of 9 days (range 4–20). Median length of follow-up was 32 months (range 21–64). Complications included three superficial perineal wound problems requiring surgery. No biological mesh weas removed and no further procedures were required. No perineal hernias have been detected. Local recurrence occurred in three patients (2 R1 and 1 R0 resection) and distant metastases in six. There was no 90-day mortality and 13% of patients died by the end of this study period. Conclusion: Reduced incidence of long term complications, including low perineal hernia rates demonstrates that pelvic floor reconstruction with a biological mesh following ELAPER without the additional use of myocutaneous flaps is both safe and feasible. Disclosure of interest: None Declared.